Fault induced problems in hydropower tunnels in Nepal: A case study - B. Chhushyabaga; S. Karki; S.S. Khadka (Lowland Technology International, 2020)
This study focuses on the fault induced problems in the hydropower tunnels in Lesser Himalaya Region of Nepal and its stability using Numerical analysis. The presence of fault in the rock mass increases the existing in-situ stress beyond its critical level and strength. Due to which squeezing, swelling in sheared, schistosed, deformed rock mass and spalling, rock bursts in intact, unjointed rock mass are frequently encountered. The existing methods of the stability analysis, estimation of tunnel support using rock mass classifications do not consider the effect of the fault. A detailed study using 2D numerical analysis is carried out using the geological data, rock mass and fault encountered in hydropower tunnel. A comparison is then made between the analysis result of the tunnel with and without the fault to actual tunnel of case study.